2010
DOI: 10.1080/02680930903447671
|View full text |Cite
|
Sign up to set email alerts
|

Citizens and/or consumers: mutations in the construction of concepts and practices of school choice

Abstract: is Reader in Education at Goldsmiths, University of London. He writes about education policy and governance and governing relations with a focus on privatisation management, meta-governance, attraction and soft governing, risk responsibility, expert administration, regulated participation, and democratic cultures. His recent books include Modernising School Governance (Routledge 2016) and Education Governance and Social Theory (Bloomsbury 2018).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 34 publications
(25 reference statements)
0
27
0
1
Order By: Relevance
“…For example, Wilkins (2010) argues against the criticism that working-class parents who choose local schools are passive and indiscriminate in making decisions for their children's education. On the contrary, he contends choosing a nearby school can be an active decision for working-class parents because of the values they attribute to the local community including 'solidarity, association, shared experience, familiarity, closeness, security, co-operation and connection' (Wilkins, 2010: 6-7).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Wilkins (2010) argues against the criticism that working-class parents who choose local schools are passive and indiscriminate in making decisions for their children's education. On the contrary, he contends choosing a nearby school can be an active decision for working-class parents because of the values they attribute to the local community including 'solidarity, association, shared experience, familiarity, closeness, security, co-operation and connection' (Wilkins, 2010: 6-7).…”
Section: Introductionmentioning
confidence: 99%
“…The literature also suggested that the reasons for a specific choice being made can be informed by the religious, ethnic and socio-economic backgrounds of parents (Ball et al, , 1996Burgess et al, 2009;Denessen et al, 2005;Hastings, Kane, & Staiger, 2005;Vincent, & Ball, 2006;Woods, 1996) and that parents differ -especially according to their socio-economic background -in the ways in which they both understand the working of the education market and subsequently engage with it (Ball et al 1996;Ball and Vincent, 1998;Raveaud and van Zanten, 2007;Wilkins 2010). …”
Section: Introductionmentioning
confidence: 99%
“…La tendencia general de estos análisis sugiere que, existiendo o no cuasimercados educativos, se produce una fuerte competencia entre los padres por matricular a sus hijos en aquellas escuelas que consideran mejores o que poseen mayor prestigio (Ball, 1997), lo que puede interpretarse como que, incluso en contextos institucionales de propiedad pública y formalmente no definidos como un mercado, muchos padres se comportan como "consumidores" de buena educación (Wilkins, 2010). Por cierto, la forma en que esto se expresa varía sensiblemente según el entorno institucional de cada país: cuando existen pocas opciones de diferenciación de la oferta y de elección de los padres, el mercado residencial termina expresando en buena medida la dinámica de competencia por mejores oportunidades educacionales (como ha sido ampliamente documentado en Estados Unidos); mientras en otros países (como en Francia), dicha competencia es canalizada a través de establecimientos públicos académicamente selectivos y de gran prestigio (Van Zanten 2010).…”
Section: La Elección De Escuela Pública: ¿El Contrafactual?unclassified
“…Research by Wilkins (2010) has highlighted complex and contradictory feelings among mothers where consumerist desires to seek 'the best' for their children come into conflict with wider senses of community responsibility. Moreover, in a context where disadvantaged parents have little real 'consumer power' in terms of school choice and so show rational ambivalence towards it, such a sense can be considered a limited market definition of empowerment or agency compared with other definitions which might promote collective voice or action (Vincent, 1996: 470) 5 and a challenging of wider social inequalities underlying the existence of 'desirable' and 'undesirable' schools.…”
Section: 'Schools Can Be Economical With the Truth With Various Thinmentioning
confidence: 99%